Cartografias da (Trans)Formação Docente: Uma Experiência Estética com o Cinema - Kerr Junior, Donald Hugh de Barros (Universidade do Vale do Rio dos Sinos, 2012)
This thesis is a result of a collection of energies that try to outline, through the use of cartography, a map of possibilities for a possible action in teachers (trans)formation. Since it is already known about the many existing methods to “form” a teacher, methods that in most of the cases privileges the memory, the return to sameness and the identity, in this thesis we ask: How to work a (trans)formation in teachers, trying to find something that is not known? How to allow an agreement when forgetfulness is what people want to bet on? How does the image of cinema strengthen the concept of art as feeling as well as its own image as short memory and crystal-image? It is considered that the way in which this thesis itself was written, with its ruptures, fragmentations and reflections may be a way of thinking about education as creation and invention. The cartography used here is based in philosophy, art, cinema, and teacher training literature. The thesis that we assume and want to demonstrate with such cartography is that the education of a teacher may be effected by the conception of art as feeling, of education as forgetfulness, and of cinema as optical image and pure sound, therefore bringing about important changes in teacher training, a process that when believed as invention and creation is always dangerous, unexpected and unpredictable.
Keywords: Cartografia; Cinema; Experiência estética; Formação de professores; Cartography; Aesthetic experience; Teacher training; ACCNPQ::Ciências Humanas::Educação